2019
DOI: 10.1002/hep.30881
|View full text |Cite
|
Sign up to set email alerts
|

4‐1BB Delineates Distinct Activation Status of Exhausted Tumor‐Infiltrating CD8+ T Cells in Hepatocellular Carcinoma

Abstract: Background and Aims Targeting costimulatory receptors with agonistic antibodies is a promising cancer immunotherapy option. We aimed to investigate costimulatory receptor expression, particularly 4‐1BB (CD137 or tumor necrosis factor receptor superfamily member 9), on tumor‐infiltrating CD8+ T cells (CD8+ tumor‐infiltrating lymphocytes [TILs]) and its association with distinct T‐cell activation features among exhausted CD8+ TILs in hepatocellular carcinoma (HCC). Approach and Results Tumor tissues, adjacent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 50 publications
3
91
1
Order By: Relevance
“…As our understanding of the functional status of T cells, particularly exhausted T cell phenotypes, in tumour-infiltrating lymphocytes and peripheral blood from patients with HCC rapidly evolves, the predictive value of biomarkers from peripheral blood should be explored, as these biomarkers may overcome limitations of sample availability. [65][66][67] The availability of pre-and post-treatment tumour samples during ICI therapy is crucial for biomarker research in HCC. There is an ongoing clinical trial of pembrolizumab, in which serial tumour biopsies are planned at baseline and after 2 cycles of treatment (NCT03419481).…”
Section: The Importance Of Predictive Biomarkersmentioning
confidence: 99%
“…As our understanding of the functional status of T cells, particularly exhausted T cell phenotypes, in tumour-infiltrating lymphocytes and peripheral blood from patients with HCC rapidly evolves, the predictive value of biomarkers from peripheral blood should be explored, as these biomarkers may overcome limitations of sample availability. [65][66][67] The availability of pre-and post-treatment tumour samples during ICI therapy is crucial for biomarker research in HCC. There is an ongoing clinical trial of pembrolizumab, in which serial tumour biopsies are planned at baseline and after 2 cycles of treatment (NCT03419481).…”
Section: The Importance Of Predictive Biomarkersmentioning
confidence: 99%
“…A study focused on hepatocellular carcinoma also revealed that TNFRSF9 was a distinct activation status marker of highly exhausted CD8 + T cells and TNFRSF9 + PD1 high CD8 + T cells exhibited higher activation markers than their TNFRSF9 − counterparts. 20 In ccRCC, higher TNFRSF9 + CD8 + T cells signature was significantly associated with higher shrinkage of tumor size and better response to ICB. This could be partly explained by the high expression of both PD-1 and effector phenotype markers in TNFRSF9 + CD8 + T cells.…”
Section: Discussionmentioning
confidence: 91%
“…18,19 Furthermore, a study on hepatocellular carcinoma has revealed that TNFRSF9 delineates a distinct activation status of exhausted tumor-infiltrating CD8 + T cells. 20 However, recent studies suggested a potential relationship between TNFRSF9 and T cells exhaustion, 8,21 which indicated the complicated role of TNFRSF9 in immune response. Also, the function of TNRSF9 + CD8 + T cells in ccRCC has not been well delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the immune heterogeneity among cancer patients is well known [22][23][24], the heterogeneity of immune subsets according to their location remains unclear. We aimed to Given that TIM3 and LAG3 are expressed on a highly activated and exhausted T cells [23], the abundance of LAG3 and TIM3 expression in the tumor margin suggests that this is the major site where the active engagement of T cells against tumor cells and resulting T cell exhaustion occur.…”
Section: Discussionmentioning
confidence: 99%